(untitled) (Italian Journal of Public Health, 2010)
Objectives and methods: We sought to determine immigrants’ level of satisfaction with health care services in western developed countries. A comprehensive literature search was conducted to identify all relevant studies that assessed patient satisfaction among this population subgroup. As the research encountered different methods and settings, results were synthesized in a narrative form. Results and conclusions: The search process yielded 54 potentially relevant (published) studies. 26 of them were excluded for reasons presented in the section Exclusion criteria. The remaining 28 were retained for analysis. Usually, immigrant patients showed lower satisfaction levels with western health services.